TCP/IP protocol suite - Forouzan, Behrouz A.; Fegan, Sophia Chung (Boston : McGraw-Hill, 2010)
"TCP/IP Protocol Suite teaches students and professionals with no prior knowledge of TCP/IP everything they need to know about this highly technical subject while avoiding complex mathematical formulae. In order to accomplish this, Behrouz Forouzan uses an extensive collection of figures to demonstrate concepts so students can grasp them intuitively. Additionally, he provides many opportunities for students to check comprehension of ideas by completing the practice sets found at the end of each chapter.
TCP/IP Protocol Suite is ideal for use in a TCP/IP course, as a second text in a networking course, or as a professional reference book."--BOOK JACKET.
Ch. 25. Next Generation: IPv6 and ICMPv6 -- App. A. ASCII Code -- App. B. Numbering Systems and Transformation -- App. C. Representation of Binary Numbers -- App. D. Error Detection -- App. E. Encryption/Decryption -- App. F. MIB Objects -- App. G. High-Level Data Link Control (HDLC) -- App. H. Project 802 -- App. I. Asn.1 -- App. J. Spanning Tree -- App. K. Contact Addresses -- App. L. RFCs -- App. M. UDP and TCP Ports.
Includes bibliographical references (p. 809-810) and index.
Keywords: TCP/IP (Computer network protocol)